Implementasi Metode Kemampuan Indera Manusia (KIM) Untuk Meningkatkan Maharah Al- Kalam - Isyanto, Nur; Abdullah, Abdullah (STAINI Press, 2022)
The impression among students in Indonesia is generally that Arabic is a difficult language to learn. This impression forms an a priori mindset of students towards Arabic. So that their participation in Arabic subjects is not motivated by curiosity but because of compulsion. Moreover, as proof of the results of learning Arabic, namely maharah al-kalam (speaking Competence), it is still very lacking so that very few students are able to express their thoughts and feelings orally. This was also experienced at Al-Ashriyyah Nurul Iman Middle School where the cause was the lack of intensive oral practice in speaking Arabic and the lack of creativity of the teacher in applying innovative learning methods. Based on previous research, one of the treatments in solving the problem is by applying the right method, namely; Game of the human senses (KIM). KIM is a method that uses the five senses to improve the intelligence of left brain thinking, this game aims to train students' memory, creativity and accuracy, in addition to developing speaking skills. This study aims to increase maharah kalam through the method of human sensory abilities (KIM) for class VIII C students of Al-Ashriyyah Nurul Iman Middle School. The research subjects were 23 students. This research is an action research, which was carried out in three cycles. The research results determined in the form of activities and student learning outcomes. Based on observation data and final test results in cycle 1, the student activity value was 11 and increased in cycle II to 21, increasing to 26 in cycle III. As for the percentage of students' complete learning outcomes on maharah kalam Arabic in the first cycle, there is no complete increase, increasing to 47.8% in the second cycle, increasing to 86.9% in the third cycle. Thus, there is an increase in maharah kalam through the method of human sensory abilities (KIM) for class VIII C students of Al-Ashriyyah Nurul Iman Middle School.